SEG Technical Program Expanded Abstracts 2011 2011
DOI: 10.1190/1.3627380
|View full text |Cite
|
Sign up to set email alerts
|

Seismic source comparison for shallow targets in north Kuwait field

Abstract: A 2D seismic reflection line for shallow targets in north Kuwait was acquired in December of 2010 with varying source types: explosives, accelerated weight drop, small (15,000 lb) vibrator, and heavy (80,000 lb) vibrator. The exploration target is shallow at around 100 ms to 400 ms two-way time (TWT). The objective of the study was to establish the optimal source effort for a planned 3D survey. The accelerated weight drop proved to be inferior to the other source types because the data lacked high-frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…A number of land seismic sources have been developed and successfully applied to accommodate these additional challenges; without compromising data quality (e.g. Meunier and Daures, 2008, Suarez and Stewart, 2009and Kumar et al, 2011. The onSEIS "Geokinetics proprietary seismic electrical impulsive source" is one of the latest developments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of land seismic sources have been developed and successfully applied to accommodate these additional challenges; without compromising data quality (e.g. Meunier and Daures, 2008, Suarez and Stewart, 2009and Kumar et al, 2011. The onSEIS "Geokinetics proprietary seismic electrical impulsive source" is one of the latest developments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of comprehensive source tests have been undertaken in the past (e.g. Yordkayhun, et al, 2008, Suarez, et al 2009, and Kumar et al, 2011. Technological advances have improved the performance of the different source types; however, the results of the previous studies showed clear differences between various seismic sources at different locations.…”
Section: Introductionmentioning
confidence: 99%
“…Такая ситуация возникает при не обходимости совместного исполвзования перекрываю щ ихся съемок, выполненных в разны х проектах или в одном проекте, например в переходных зонах суша-мо ре [Hesthammer, Lokkebo, 1997;M ohan et al, 2007;Carter, Pambayuning, 2009;Greer, Fomel, 2018;. Кроме того, с этим прихо дится сталкиватвся при тестировании различных сейсмических источников Kumar et al, 2011;.…”
unclassified